Long-term Follow-up of Trigger Point Injections for Abdominal Wall Pain - Jose Nazareno; Terry Ponich; Jamie Gregor (Canadian Journal of Gastroenterology)
OBJECTIVE: Abdominal wall pain (AWP) is a common yet often overlooked source of abdominal pain. Trigger point injections (TPI) into the abdominal wall have been tried in the past. Few studies have looked at the long-term outcome from these injections.